Religious Harmony Within Ahmadiyah Community: (Study of Living Qur'an and the Peace Construction in the Village of Gondrong Kenanga - Adrika Fithrotul Aini (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
In the midst of intolerant attitudes toward Ahmadiyah, the community of Ahmadiyah in Gondrong Kenanga present as a villagers that value diversity. Not only Ahmadiyah followers but also many other groups live in the village, such as Muslims affiliated to NU, Muhammadiyah, and other groups of religious believers. Interstingly, in everyday life they are able to protect themselve from getting involved in conflict and creating a peaceful and harmonious life. Harmony in the village Gondrong appears in at least two forms including in the pattern of inter-community relations in the environment and in daily life interction of people reflected in the social environment. Gondrong Ahmadiyah community is actively involved in various social activities that promote tolerance, cooperation, and solidarity. The work aims at getting the concept of peace in the Ahmadiyah community in Gondrong Kenanga. This study also examines the living Qur’an regarding the understanding of the concept of pluralism and harmony within Ahmadiyah members. This work is based on a field research project on the phenomenon of living Qur’an studies that examines the understanding of the Islamic teaching on diversity by the Jamaah Ahmadiyah Indonesia of Gondrong-kenanga (JAIG), and also the construction of peace which is practiced in their daily life.